DED process parameters optimization via experiments - Shaik Siraaj Muneer bin Mohammed Shaik Yamani (Nanyang Technological University, 2024)
Additive Manufacturing (AM) is a manufacturing technology that is being leveraged increasingly in an expanding number of industries. The resulting microstructure of a metallic material due to the Additive Manufacturing process could potentially cause it to possess different mechanical properties, good and bad, from its classically produced alternative. In this report, the compressive behaviour of heterogenous AM 316L Stainless Steel stubs to determine their compression performance and highlight their deformation mechanisms during the compression testing to compare it to that of conventionally produced 316L Stainless Steel documented in the literature to discuss whether AM technology is robust enough to be used as an alternative to extruding said materials in a practical setting. For this project, 20 samples of AM 316L Stainless Steel underwent compression testing at room temperature and the data from the compression tests were obtained and refined to provide a more clearly defined Force/Displacement and Stress/Strain curves for further analysis. The results obtained from the experiments showed that the AM samples exhibited deviances from conventional 316L Stainless Steel in specific mechanical properties, such as ductility and Young’s Modulus. Differences in ultimate compressive strength, yield point and plastic deformation were also noted. The study implies that crystalline metallic structures produced by AM exhibit unique properties to traditionally produced metals, which allow for novel use cases and further property optimisation through the AM process.